Numerical modelling of the thermal response of pultruded GFRP tubular profiles subjected to fire. (15th March 2018) - Morgado, T.; Silvestre, N.; Correia, J.R.; Branco, F.A.; Keller, T.
Abstract: This paper presents a numerical study about the thermal behaviour of pultruded GFRP profiles with square tubular cross-section exposed to fire. Two-dimensional and three-dimensional numerical models of previous fire tests of GFRP profiles were developed using the commercial software ANSYS Fluent 14.5 . The efficacy of using different fire protection systems (passive and active) and the influence of the number of sides exposed to fire (one or three) in the thermal response of the GFRP profiles was studied. The models developed consider the heat exchanges by means of conduction, internal radiation and convection of the air and/or water enclosed in the cavity of the GFRP tubular profiles. A general good agreement was obtained between numerical temperatures and test data. The results obtained highlight (i) the relative efficiency of the different fire protection systems and (ii) the remarkable influence of exposing GFRP profiles to fire in three sides, and (iii) show the importance of the heat exchanges due to internal radiation and convection inside the cavity of the GFRP cross-section in this type of thermal simulations. The thermal models were further validated through the simulation of previous fire resistance experiments on multicellular slab panels.